The Role of Natural of AntisenseTranscription HAGLR,LCMT1AS, NAV2AS5,TSIX in Breast Cancer (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Background: lncRNAs (longnon-codingRNAs), has various important molecular and cellular functions and natural antisense transcripts (NATs), complementary to protein-coding or non-coding. RNA sequences are important regulators of gene expression drew great attention in recent years to uncover their importance for diagnostic, prognostic and therapeutic purposes; and their dysfunctions lead to diseases including cancer.Aims: The aim of this study was to investigate important roles of lncRNA TSIX, HAGLR, LMCT1AS and NAV2AS5 genes in several tumorigenic processes in breast cancer.Materials and methods: In this study, we used ATCC normal cell lines (CRL4010,CRL8798) and cancer cell lines (MCF7,MDA-MB231,CRL2329) that subjected. To examine through RNA isolation,cDNA conversion, semiquantitative (by agarose gel and ImageJ program) and quantitative RT-PCR for gene expression analyses.Results: Our results have been shown that TSIX, HAGLR, LMCT1AS, and NAV2AS5 genes have differential expression pattern in both normal and breast cancer cell lines.Conclusion: from the data of our results we concluded that these genes have an important role in biological processes of breast cancer, in addition, to their importance in the treatment and therapeutic purposes.